Brick manufacturing practice in Bangladesh: a review of energy efficacy and air pollution scenarios - Darain, Kh Mahfuz ud; Rahman, A. B. M. S.; Ahsan, Amimul; Saiful Islam, A. B. M.; Yusuf, Badronnisa (EnviroWater Sydney, 2013)
Building structures and major construction works are booming in the urban areas of Bangladesh to keep up the rapid urbanization rate. Brick is an essential construction material for its building industries. To meet the need of construction, brickfields are growing sporadically here and there at the fringe zones and within the urban regions. Eventually, brickfields are producing major environmental pollutants. This paper highlights existing technologies of brick manufacturing as well as their emission which exceeds the tolerable limit and puts a threat to the environment. Treatise is also portrayed regarding techniques which could help minimizing the drawback of existing brick kiln technologies. Vertical Shaft Brick kiln might be an altern ative solution for the small investors in Bangladesh which is energy efficient and can minimize the air pollution to achieve a sustainable environment.